Effects of Addition of Skipjack Meat to Water Levels, Protein Levels and Ash Levels of Floss Sweet Corn - mutia, khairun (Jurnal Ilmu Pangan dan Hasil Pertanian, 2020)
The aim of this study was to determine the concentration of tuna fish that can produce shredded which has good quality. The method used in this study was a completely randomized design (RAL) with 3 treatments and 3 replications. The treatments in this study were A1 (375 g of skipjack meat) A2 (250 g of skipjack meat) and A3 (125 g of skipjack meat). The results of this study resulted that A3 treatment with a concentration of 125 g of skipjack fish meat provided good quality fish with a water content of 7,17%, ash content of 2,72% and protein content of 33,22%.